Does the presence of certain bacterial family in the microbiome indicate specific indoor environment characteristics? A factorial design approach for identifying bio-fingerprints. Issue 1 (January 2020) - Seong, Dahae; Hoque, Shamia
The study applies the current knowledge on microbiome in built environments towards identifying microbes, specifically bacteria as bio-fingerprints which can reflect indoor space and occupant characteristics. Data were collected from the literature on the bacterial family and the indoor environment. The factorial design approach was applied to quantify and compare the influence of selected indoor environmental parameters, sampling region (air or surface), sampling locations (residence or non-residence), gender and age and their interactions on the types and concentration of detected bacterial families. Factorial design analysis identified and confirmed Corynebacteriaceae and Lactobacillaceae as the gender signature for males and females, respectively. The significant bacterial families across all scenarios are: Corynebacteriaceae, Propionibacteriaceae, Bacillaceae, Staphylococcaceae, Lactobacillaceae, Methylobacteriaceae, Moraxellaceae, Micrococcaceae, Enterobacteriaceae, Rhodobacteraceae, Streptococcaceae and Pseudomonadaceae . Higher concentrations of Propionibacteriaceae indicate that the specific location is an adult-occupied space. Staphylococcaceae presence is the bio-fingerprint of contaminated air of hospitals bio-fingerprint and Moraxellaceae on hospital surfaces are distinct characteristics. Streptococcaceae is a bio-fingerprint of contaminated air of schools and other children-occupied spaces. Enterobacteriaceae is a bio-fingerprint of contaminated air of non-residence locations. Bacillaceae does not indicate any indoor characteristics.